Inter-adsorbate forces and coherent scattering in helium spin-echo experiments. Issue 13 (14th October 2020) - Ward, David J.; Raghavan, Arjun; Tamtögl, Anton; Jardine, Andrew P.; Bahn, Emanuel; Ellis, John; Miret-Artès, Salvador; Allison, William
Abstract : Using helium atom scattering to identify adsorbate interactions and separate the effects of long and short range forces. Abstract : In studies of dynamical systems, helium atoms scatter coherently from an ensemble of adsorbates as they diffuse on the surface. The results give information on the co-operative behaviour of interacting adsorbates and thus include the effects of both adsorbate–substrate and adsorbate–adsorbate interactions. Here, we discuss a method to disentangle the effects of interactions between adsorbates from those with the substrate. The result gives an approximation to observations that would be obtained if the scattering was incoherent. Information from the experiment can therefore be used to distinguish more clearly between long-range inter-adsorbate forces and the short range effects arising from the local lattice potential and associated thermal excitations. The method is discussed in the context of a system with strong inter-adsorbate interactions, sodium atoms diffusing on a copper (111) surface.